The Impact of Teachers' Pedagogical and Professional Competence on Student Learning Outcomes - Mujiyatun Mujiyatun; Nyayu Khodijah; Abdurrahmansyah Abdurrahmansyah (STAI Hubbulwathan Duri, 2021)
This study aimed to analyze the effect of teachers' pedagogic competence and professional competence on the quality of learning and student learning outcomes in fiqh subjects. The method used in this research was quantitative to see the causal relationship between research variables. The population and samples used in the study were 51 teachers of fiqh subjects in the South Lampung Regency. Data were collected through a questionnaire. The method of data analysis was done by path analysis. The study showed that first, pedagogic competence positively correlated to the quality of the learning process by 31%. Second, professional competence positively correlated to the quality of the learning process by 18%. Third, pedagogic competence and professional competence positively correlated to the quality of the learning process by 36%. Fourth, pedagogic competence positively correlated to learning outcomes by 37%. Fifth, professional competence positively correlated to learning outcomes by 19%. Sixth, pedagogic competence and professional competence positively correlated to learning outcomes by 30%. Seventh, the learning process positively correlated to learning outcomes by 16%. Thus, teachers' pedagogic competence and professional competence affected the quality of the fiqh learning process and student learning outcomes. Therefore, teachers were expected to improve their pedagogic and professional competencies continuously.